Collaborative Strategies of Teachers and Parents in Fostering Discipline among Students: A Comparative Study of Muslim Minority Countries in Southeast Asia - Tadol, Nor-Hayna Dasad; Neem, Chuti (Khalifa Journal of Islamic Education, 2024)
This study aims to explore how Quran teachers and parents discipline students to perform the dawn prayer. The study employs a qualitative method with a case study approach. Data were collected from ten informants through in-depth interviews. The informants consisted of Quran teachers, parents, and students. Data collection techniques included interviews and observation. All interview results were then analyzed thematically using NVivo 12 qualitative analysis software. Overall, the findings show that there are seven efforts made by Quran teachers and parents to encourage students to perform the dawn prayer. These seven efforts are divided into four actions by Qur’an teachers to instill discipline in students to participate in religious activities, namely: (i) imposing sanctions, (ii) giving rewards, (iii) conducting discussions between teachers and parents, and (iv) providing advice. Meanwhile, three efforts were made by parents to instill discipline in students to participate in religious activities, namely: (v) teaching children about the importance of the dawn prayer and how to perform it at home, (vi) providing motivation and rewards, and (vii) explaining the benefits of the dawn prayer to children. The results of this study can serve as preliminary data for future researchers to examine other issues related to this topic or similar contexts.